From Tarlabaşı to Gezi and beyond: The 2013 Event in the Conjuncture of Neoliberal times - Voulvouli, Aimilia (The Greek Review of Social Research, 2018)
Drawing on ethnographic material from Istanbul prior and during the Gezi uprising of 2013, the present article examines the mass demonstrations that broke out in more than 90 cities in Turkey and lasted for about a month as an event in the sense of the short duration of history (évènement) informed by historical processes of medium length duration (conjoncture) marked by authoritarianism and protest; an event bearing the inevitability of rupture that long-term authoritarianism carries to the present and also the future; a product of a culture of protest traced back to the 1980s and the neoliberal restructuring of the Turkish economy. Furthermore, the paper discusses the rise of the electoral influence of the Democratic People’s Party (Halkların Demokratik Partisi - HDP) as a symptom of the same historical conjuncture.